Evaluasi Kualitas Website dengan Metode Webqual (Studi Kasus: Website Teknik Informatika Universitas Pamulang) - Atang Susila; Dede Sahrul Bahri (Teknik Informatika Universitas Pamulang, 2023)
The development of the use of the internet is currently very rapid and has resulted in many changes in the order of people's lives, including educational institutions that use the internet by building websites for their business process needs. The Informatics Engineering Study Program, Faculty of Computer Science, Pamulang University is a quite large study program in terms of the number of students who have a website as a form of communication with its users, be it lecturers, students, and the community in general, but from the analysis results it is still not optimal in its utilization. Therefore the first step taken is to evaluate the extent of student satisfaction with the quality of the website. The measurement process is carried out through an assessment by Informatics Engineering Study Program students through a questionnaire prepared according to the WebQual 4.0 device. This method was chosen because it is one of the methods or techniques used to measure website quality based on the end user's perceived quality in three areas, namely Information Quality, Service Interaction Quality, and Usability. The measurement results obtained that Usability, Information Quality, and Interaction Quality together had a very positive and significant effect on student satisfaction and could explain the satisfaction variable of 86.7% while the remaining 13.3% was another factor.